Fisetina, um flavonóide que protege camundongos do dano neuronal e déficit de memória induzido por isquemia cerebral focal permanente - Silva, Ana Thais Araújo da (2016)
Stroke is a common disease and a major cause of death and disability worldwide. The focal ischemic stroke (ischemic stroke) occurs due to a reduced blood supply to brain region, leading to the decrease of oxygen and glucose in tissues, inducing a cascade of events including oxidative stress and inflammation, culminating with neuronal death and thus a rapid loss of neurological function. Fisetin is a member of subgroup belonging to the flavonol flavonoid found in many fruits and vegetables that have anti-inflammatory and antioxidant properties. The objective of this work was to study the effects of fisetin on neuronal damage and memory, inflammatory response and synaptogenesis in mice undergoing experimental model of permanent focal cerebral ischemia (pMCAO). Were animals divided between the false-operated groups treated with vehicle or fisetin (SIF) at a dose of 50 mg / kg-ischemic treated with vehicle and-ischemic treated with FIS in doses of 10, 30, and 50 mg / kg po 3 hours after the middle cerebral artery electrocautery. The permanent focal cerebral ischemia model was proven by the significant increase in infarct area and sensorimotor deficits in- ischemic animals, observed by staining with TTC and neurological evaluation. Fisetin was able to reverse these effects by decreasing the ischemic area and sensorimotor deficits. The- ischemic animals showed changes in horizontal locomotor activity, only vertically and fisetin was able to reverse this effect. The pMCAO induced deficits in working memory, aversive, episodic and spatial memory in animals. Fisetin reversed the deficits in working memory, episodic and space at a dose of 50 mg / kg, but in the evaluation of aversive memory fisetin failed to reverse these deficits. The pMCAO caused an increase in astrocyte activation and TNF-α levels (in the striatum) and fisetin at a dose of 50 mg / kg was able to decrease the activation of astrocytes and TNF-α but not the levels. We also observed a decrease in synaptophysin expression in the striatum of animals-ischemic and fisetin could raise these levels. The pMCAO decreased BDNF levels in the striatum and increased in the hippocampus of fisetin-ischemic animals and the dose of 50mg / kg was able to reverse these levels in the striatum. The results of this study suggest that fisetin has neuroresgate action, improving neuronal injury, neurological disorders and memory deficits caused by ischemia. These effects are possibly their anti-inflammatory actions.